Association Between Change in Serum Aminotransferase and Mortality: A Nationwide Cohort Study in Korea. Issue 12 (March 2016) - Lee, Hyejin; Shin, Dong Wook; Lee, Tae Hoon; Yang, Hyung-Kook; Ahn, Eunmi; Yoon, Jae-Moon; Lee, Hyun-Ki; Suh, Beomseok; Son, Ki Young; Kim, Jun Suk; Cho, BeLong
Abstract : Abstract: There is little information on how the change in serum aminotransferase affects mortality. We investigated the association between changes in serum aminotransferase levels and mortality from all causes, cardiovascular disease (CVD), and liver disease. Three percent of men from the Korean National Health Insurance database were sampled randomly at the end of 2002. After excluding patients with cancer, CVD, CVD risk factors, or liver disease, those who participated in 2 consecutive rounds of the national health screening examination were included (n = 68, 431). The primary outcome was CVD mortality. Secondary outcomes were liver disease mortality and all-cause mortality. Change in metabolic profiles was analyzed based on changes in liver enzyme levels. Elevated levels of serum aminotransferase were associated with CVD, liver disease, and all-cause mortality. Men who had sustained elevation of serum aminotransferase during 2 subsequent liver enzyme tests showed a significantly higher risk of CVD mortality (adjusted hazard ratio [aHR] 1.95; 95% confidence interval [CI] 1.07–3.56, 2.29; 1.27–4.12) than the sustained normal group. In contrast, the normalization group (aHR 1.52, 95% CI 0.82–2.81 for aspartate aminotransferase [AST]; aHR 1.35, 95% CI 0.70–2.61 for alanine aminotransferase [ALT]) and the new elevation group (aHR 1.27, 0.66–2.44 for AST; aHR 0.99, 95% CI 0.49–2.20 for ALT) were not different from the sustained normal group in CVD mortality. Individuals with serum aminotransferase elevation, particularly when sustained, are at higher risk of mortality, and should receive appropriate medical attention. Abstract : Supplemental Digital Content is available in the text